Multi-molecular tracers of terrestrial carbon transfer across the pan-Arctic: comparison of hydrolyzable components with plant wax lipids and lignin phenols - X. Feng; Ö. Gustafsson; R. M. Holmes; J. E. Vonk; B. E. van Dongen; I. P. Semiletov; O. V. Dudarev; M. B. Yunker; R. W. Macdonald; D. B. Montluçon; T. I. Eglinton (Biogeosciences, 2015)
Hydrolyzable organic carbon (OC) comprises a significant component of sedimentary particulate matter transferred from land into oceans via rivers. Its abundance and nature are however not well studied in Arctic river systems, and yet may represent an important pool of carbon whose fate remains unclear in the context of mobilization and related processes associated with a changing climate. Here, we examine the molecular composition and source of hydrolyzable compounds isolated from sedimentary particles derived from nine rivers across the pan-Arctic. Bound fatty acids (b-FAs), hydroxy FAs, n-alkane-α,ω-dioic acids (DAs) and phenols were the major components released upon hydrolysis of these sediments. Among them, b-FAs received considerable inputs from bacterial and/or algal sources, whereas ω-hydroxy FAs, mid-chain substituted acids, DAs, and hydrolyzable phenols were mainly derived from cutin and suberin of higher plants. We further compared the distribution and fate of suberin- and cutin-derived compounds with those of other terrestrial biomarkers (plant wax lipids and lignin phenols) from the same Arctic river sedimentary particles and conducted a benchmark assessment of several biomarker-based indicators of OC source and extent of degradation. While suberin-specific biomarkers were positively correlated with plant-derived high-molecular-weight (HMW) FAs, lignin phenols were correlated with cutin-derived compounds. These correlations suggest that, similar to leaf-derived cutin, lignin was mainly derived from litter and surface soil horizons, whereas suberin and HMW FAs incorporated significant inputs from belowground sources (roots and deeper soil). This conclusion is supported by the negative correlation between lignin phenols and the ratio of suberin-to-cutin biomarkers. Furthermore, the molecular composition of investigated biomarkers differed between Eurasian and North American Arctic rivers: while lignin dominated in the terrestrial OC of Eurasian river sediments, hydrolyzable OC represented a much larger fraction in the sedimentary particles from Colville River. Hence, studies exclusively focusing on either plant wax lipids or lignin phenols will not be able to fully unravel the mobilization and fate of bound OC in Arctic rivers. More comprehensive, multi-molecular investigations are needed to better constrain the land–ocean transfer of carbon in the changing Arctic, including further research on the degradation and transfer of both free and bound components in Arctic river sediments.